The crystal structure of fac-tricarbonyl((pyridin-2-yl)methanamino-κ2 N,N′)-((pyridin-2-yl)methanamino-κN)rhenium(I) nitrate, C15H16O3N4Re - Ramoba Lesetja V.; Alexander Orbett T.; Malan Frederick P.; Manicum Amanda-Lee E. (Zeitschrift für Kristallographie - New Crystal Structures)
C15H16O3N4Re, triclinic, P1̄ (no. 2), a = 7.4939(2) Å, b = 10.1316(2) Å, c = 13.8351(3) Å, α = 103.453(2)°, β = 101.992(2)°, γ = 107.880(2)°, V = 926.98(4) Å3, Z = 2, R gt(F) = 0.0341, wR ref(F 2) = 0.0861, T = 150 K.